Introduction to Climate Information Services: AGNES Leadership Course on Climate Governance, Diplomacy, and Negotiations (Module 6 – Decision Support Tools) - Gamoyo, Majambo Jarumani (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This presentation, which was delivered as part of the AGNES Leadership Course on Climate Governance, Diplomacy, and Negotiations in April 2025, introduces the concept and strategic value of Climate Information Services (CIS) as essential tools for anticipatory climate action and decision-making in climate-sensitive sectors such as agriculture. It outlines the four foundational pillars of CIS—generation, translation, transfer, and use—and explains how CIS enables governments, institutions, and communities to proactively plan for and respond to climate risks. Real-world applications are highlighted through participatory approaches such as PICSA and Participatory Scenario Planning (PSP), demonstrating how tailored, localized, and inclusive climate services—co-developed with stakeholders—can enhance resilience, integrate indigenous knowledge, and support inclusive governance across Africa.